2014
DOI: 10.1016/j.jbankfin.2013.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Does bank market power affect SME financing constraints?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
134
2
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 220 publications
(177 citation statements)
references
References 24 publications
(26 reference statements)
16
134
2
13
Order By: Relevance
“…Love and Peria (2015) [38] studied from another point of view and found that the lower the internal competition of the banking industry is, the greater the hindrance to the enterprise financing will be, and this process is affected by the credit information sharing mechanism. Robert, Conor, and Fergal (2014) [39] and Demirg-Kunt A., Feyen E., and Levine R. (2013) [40] focused on the small and medium sized enterprises in developed countries and believe that the market power of the banking industry is able to effectively alleviate the financing constraints of small-and medium-sized enterprises. Mercieca, Schaeck, and Wolfe (2009) [41] studied the banking structure in Europe and found that the enhancement of the fierce competition in the banking industry will be able to increase the financing of small-and medium-sized enterprises, and the enhancement of the concentration of the banking industry will be able to reduce the financing of small-and medium-sized enterprises.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Love and Peria (2015) [38] studied from another point of view and found that the lower the internal competition of the banking industry is, the greater the hindrance to the enterprise financing will be, and this process is affected by the credit information sharing mechanism. Robert, Conor, and Fergal (2014) [39] and Demirg-Kunt A., Feyen E., and Levine R. (2013) [40] focused on the small and medium sized enterprises in developed countries and believe that the market power of the banking industry is able to effectively alleviate the financing constraints of small-and medium-sized enterprises. Mercieca, Schaeck, and Wolfe (2009) [41] studied the banking structure in Europe and found that the enhancement of the fierce competition in the banking industry will be able to increase the financing of small-and medium-sized enterprises, and the enhancement of the concentration of the banking industry will be able to reduce the financing of small-and medium-sized enterprises.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In light of the European banking consolidation in recent years, this may be a real problem in the life of smaller companies. The other factor is the potential fall in property prices, which may set SME financing back as many firms offer real estate as collateral in exchange for the loan (Chen 2006;Ryan 2014).…”
Section: Anomalies Affecting External Financingmentioning
confidence: 99%
“…In a study including 118.000 SMEs in Europe in the period of 2005-2008, "[...] investment is sensitive to the availability of internal funds and interprets this as being indicative of a wedge between the cost of internal and external financing" [Ryan, O'Toole, McCann 2014]. To finance the fixed assets by using long-term sources of investment is crucial to avoid liquidity problems.…”
Section: Financing Problems Of Smes In the European Unionmentioning
confidence: 99%